Integration of the noncollinear antiferromagnetic metal Mn3Sn onto ferroelectric oxides for electric-field control. (December 2019) - Wang, Xiaoning; Feng, Zexin; Qin, Peixin; Yan, Han; Zhou, Xiaorong; Guo, Huixin; Leng, Zhaoguogang; Chen, Weiqi; Jia, Qiannan; Hu, Zexiang; Wu, Haojiang; Zhang, Xin; et al.
Abstract: Noncollinear antiferromagnetic materials have received dramatically increasing attention in the field of spintronics as their exotic topological features such as the Berry-curvature-induced anomalous Hall effect and possible magnetic Weyl states could be utilized in future topological antiferromagnetic spintronic devices. In this work, we report the successful integration of the antiferromagnetic metal Mn3 Sn thin films onto ferroelectric oxide PMN-PT. By optimizing growth, we realized the large anomalous Hall effect with small switching magnetic fields of several tens mT fully comparable to those of bulk Mn3 Sn single crystals, anisotropic magnetoresistance and negative parallel magnetoresistance in Mn3 Sn thin films with antiferromagnetic order, which are similar to the signatures of the Weyl state in bulk Mn3 Sn single crystals. More importantly, we found that the anomalous Hall effect in antiferromagnetic Mn3 Sn thin films can be manipulated by electric fields applied onto the ferroelectric materials, thus demonstrating the feasibility of Mn3 Sn-based topological spintronic devices operated in an ultralow power manner. Graphical abstract: Image, graphical abstract